Prior failures, laboring in vain, and knowing when to give up: Incremental versus entity theories - Bae, Jin Hee; Hong, Seok-sung; Son, Lisa K. (Springer Verlag, 2021)
Against intuition, a set of "desirable difficulties" has been touted as a way in which to improve learning and lengthen retention. This includes, for instance, varying the conditions of learning to allow for more active, effortful, or challenging, contexts. In the current paper, we introduce data that show that, on the contrary, learning to know when to take the easy road may be crucial when it comes to avoiding "laboring in vain." We presented participants with prior problems - either easy or difficult - followed by choices of selecting an easy or a difficult current problem. Our primary goal was to examine the notion that past failures (which are more likely on the difficult prior items) may be a basis for allowing learners to then choose the easy rather than the difficult current problem. In other words, if one has labored in vain already, the easier items may now be more desirable. In addition, we compare the selections that are made between incremental and entity perspectives, given their fundamentally opposing views on effort. Our results showed that, interestingly, incremental theorists, who generally are proponents of effort, were more likely to select the easy problems, but only when they had experienced failure on prior, and similar, difficult tasks. We interpret these data to suggest that those holding an incremental view may be more in tune with their past efforts, resulting in a Metacognition-by-Experience, or ME strategy, and also hint at its generalizability through cross-cultural comparisons.